Emotional Compass: Exploring the Socio-Emotional Wealth's Role in Guiding Change Implementation in Family Enterprises! (Global Journal of Management and Business Research, 2024)
This research delves into the intricate impact of socio-emotional wealth (SEW) on the behavioral patterns of family firms during the implementation of organizational change. Employing the ambidexterity theory as a conceptual framework, the study scrutinizes 200 responses from proprietors and managers of family firms through a vignette-based investigation. The outcomes illuminate SEW as a pivotal guiding principle and determinant in the decisionmaking processes related to change. SEW is identified not only as an originating factor but also as a resultant outcome of change dynamics. Family firms demonstrate a propensity to embrace change in anticipation of potential advantages in terms of SEW, juxtaposed with a hesitancy when confronted with perceived risks. Furthermore, the study underscores a continuous reciprocal influence that characterizes the dynamic interplay between SEW and change. This influence extends beyond specific stages, permeating strategic and operational realms within the organizational context.
Keywords: socio-emotional wealth; change manage-ment; organizational ambidexterity; family firms